Use of alternative water sources in irrigation: potential scales, costs, and environmental impacts in California. (28th May 2020) - Qin, Yuwei; Horvath, Arpad
Abstract: Under the risk of drought, unreliable water supplies, and growing water demand, there is a growing need worldwide to explore alternative water sources to meet the demand for irrigation in agriculture and other outdoor activities. This paper estimates stocks, production capacities, economic costs, energy implications, and greenhouse gas (GHG) emissions associated with recycled water, desalinated brackish and seawater, and stormwater in California, the largest US state and the most significant fresh and processed food producer. The combined recycled water and stormwater supply could increase the share of alternative water use in urban land irrigation (parks and golf courses) from the current rate of 4.6% to 48% and in agriculture from 0.82% to 5.4% while increasing annual water costs by $900 million (1.8% of California's annual agricultural revenue) and energy use by 710 GWh (0.28% of California's annual electricity consumption). The annual supply of alternative water greatly exceeds the amount of water currently used in the food processing industry. In case studies of high-value agricultural produce, conventional water use was found to contribute approximately 17%, 12%, 4.1%, and 1.7% to the total GHG emissions of avocados, lemons, celery, and strawberries, respectively. However, materials (mostly packaging) contribute 46%, 26%, 47%, and 66%, and diesel use on farms 18%, 28%, and 14% for lemons, celery, and strawberries, respectively (data for avocados were not available). Switching to recycled water or stormwater would increase the total GHG emissions of one serving size of packaged strawberries, celery, lemons, and avocados by 3.0%, 7.8%, 11%, and 27%, respectively, desalinated brackish water by 23%, 58%, 150%, and 210%, and desalinated seawater by 35%, 88%, 230%, and 320%. Though switching to alternative water will increase costs, energy demand, and GHG emissions, they could be offset by turning to less environmentally damaging materials in agricultural production and sales (especially packaging).